2012
DOI: 10.5402/2012/463620
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Manifestations of Rheumatological Conditions: A Narrative Review

Abstract: Cardiovascular diseases are common in systemic rheumatologic diseases. They can be presented at the time of diagnosis or after diagnosis. The cardiac involvements can be the first presentation of rheumatologic conditions. It means that a patient with rheumatologic disease may go to a cardiologist when attacked by this disease at first. These manifestations are very different and involve different structures of the heart, and they can cause mortality and morbidity of patients with rheumatologic diseases. Cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 98 publications
0
47
0
1
Order By: Relevance
“…Not all myocardial manifestations of rheumatological conditions are clinically relevant, but myocardial involvement can confer considerable morbidity and mortality 38,63…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…Not all myocardial manifestations of rheumatological conditions are clinically relevant, but myocardial involvement can confer considerable morbidity and mortality 38,63…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…Approximately 1 to 2 per 1000 among whites are affected by AS, with a 3:1 to 4:1 male predominance. Its onset is usually in the third to fourth decades 1. A previous case of AS with recurrent pleural and pericardial effusion which the patient responded to prednisolone treatment was reported in literature 2.…”
Section: Discussionmentioning
confidence: 99%
“…Categorised as a seronegative spondyloarthropathy, the underlying disease process entails inflammation of the enthesis, sites where tendons and ligaments attach to bone 1. As a systemic disease, it may have other manifestations such as uveitis, fibrocavitary apical lung lesions and cardiac manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Likely one of the most well established cardiac manifestations of (RA) is premature atherosclerosis and ischemic heart disease leading to disproportionate mortality in RA due to Cardiovascular Disease (CVD) [1][2][3][4]. Studies have shown greater than two-fold increase in myocardial infarction and worse outcomes compared to controls [5][6][7][8][9].…”
Section: Atherosclerosismentioning
confidence: 99%